Mananoligossacarídeo em dietas para larvas e juvenis de tilápia do Nilo (Oreochromis niloticus) - Schwarz, Kátia Kalko (2009)
Two works were carried out to evaluate mannanoligosaccharides (MOS) inclusion in Nile tilapia (larvae and juveniles) on performance and gut morphology. In the first work, Nile tilapia larvae (n = 1500, P = 0.01 ± 0.,001g) were randomly distributed in 30 tanks of 100 liters each, for 30 days. The fish were distributed in a randomized block design with six treatments and with five replicates. The control diet was elaborated to contain approximately 35% of crude protein and 3,100 kcal DE/kg and MOS was included at 0, 0.15, 0.30, 0.45, 0.60 and 0.75% of diet. In the second work a total of, 224 fish with an average initial weight of approximately 25 g were distributed in a randomized blocks design, as block was considered each tank of 1,000 L with four cages (0.12 m3 each), with one cage from each treatment. A recirculation systems (10 L/minute/tank) with supplemental aeration and a biofilter was used. The fish were fed manually, four times a day byfor 53 days. A control diet with 28.5% crude protein and 2855 kcal of digestible energy/kg was used and MOS was included at 1, 2 and 3% of the control diet. The apparent digestibility coefficients were determined by modified Guelph method using chromic oxide as inert indicator. In the first work, a linear increase on the intestine length, intestinal villous height and villi density was observed according to the dietary MOS inclusion. No differences of dietary MOS on body composition, weight gain, weight final, final length, condition factor, survival and number of goblet cells of the gut of the larvae were observed. A quadratic effect on feed conversion ratio was observed with according to the MOS inclusion and the best value was estimated with 0.34%, respectively. In the second work, no effects of MOS on feed intake, hepatossomatic index, survival, body moisture and ash, apparent digestibility coefficients of dry matter, gross energy, crude protein, ether extract and ash availability and number of goblet cells per villus were observed. The best values of feed intake, feed conversion ratio, protein efficiency ratio, and body composition were observed in fish fed with 1% of dietary MOS. It was concluded that 0,34% and 1% of dietary MOS is adequate for Nile tilapia, larvae and juveniles, respectively.